Self-interference Cancellation Technique Using Circular Polarization For Full-duplex Wireless Communication System In 5g Technology - Endah Setyowati; Rina Pudji Astuti; Bambang Setia Nugroh (eProceedings of Engineering, 2015)
Self-interference occurred due to implementation of single channel full-duplex, where the transmit signal interfere the receive signal in the same node. The previous work [2] has been studied the passive cancellation, but those techniques only against the direct path. Then proposed a method using directional antenna with circular polarization to solve self-interference issue. The use of different circular polarization type on transmitter and receiver gives better quality against self-interference. In free space loss channel, using this method obtain polarization loss factor (PLF) as 0 means self-interference totally eliminated. However, AWGN channel gives effect that change polarization shape that results PLF not same as 0. The alpha - comparison between side lobe and main lobe power at directional antenna- makes impact on system performance. For obtaining bit error rate (BER) 10-3 needs SINR 17.04 dB, 16.29 dB, and 16.05 dB with alpha value 10-0.5, 10-1, and 10-2.5. Keywords—single channel full-duplex, self-interference cancellation, circular polarization.